Interest-rate exposure and bank mergers - Esty, Benjamin; Narasimhan, Bhanu; Tufano, Peter (Journal of Banking & Finance, 1999)
This study examines how interest rates and interest-rate exposures affect the level of acquisition activity, the identities of targets and acquirers, and the pricing of acquisitions in the banking industry. Using a sample of 477 large mergers from 1980 to 1994, we find that the level of acquisition activity is more positively correlated with equity indices and more negatively correlated with interest rates for banks than for non-banks. Although we find that targets and acquirers have significantly different interest-rate exposures, we find little evidence that one group is consistently better or worse positioned, ex post, for various interest-rate environments. Finally, we find some evidence that merger pricing is a function of the interest-rate environment, with acquirers paying higher prices and earning lower returns when rates are low (and when more deals are announced).